Fetal therapy of LUTO (lower urinary tract obstruction) – a follow-up observational study. (12th December 2022) - Keil, Corinna; Bedei, Ivonne; Sommer, Lara; Koemhoff, Martin; Axt-Fliedner, Roland; Köhler, Siegmund; Weber, Stefanie
Abstract: Purpose: Fetal megacystis (MC) can be severe and is mainly caused by fetal lower urinary tract obstruction (LUTO). Mortality of fetal LUTO can be high as a result of pulmonary hypoplasia and/or (chronic) renal insufficiency. Several technical procedures for vesicoamniotic shunting (VAS) were developed to improve fetal MC outcomes. Material and methods: We present the outcome of nine fetuses with MC who received VAS in the prenatal period (14 + 6 to 27 + 6 weeks GA) using the Somatex ® intrauterine shunt system. MC was defined as an increased longitudinal measurement of the bladder >15 mm. The median follow-up time after birth was 18 months. Results: Eight Fetuses had uncomplicated VAS intervention. One case developed PPROM 24 h after VAS leading to abortion. Pregnancy was later terminated in further two cases. All six live-born infants received intensive care treatment. Invasive-mechanical ventilation was necessary in one case who died 24 h post-partum of severe cardiac depression. Five infants who survived the follow-up time developed chronic renal insufficiency (CRI), with one infant developing end-stage renal failure requiring peritoneal dialysis. Conclusion: Overall, 5 of 9 LUTO fetuses (55%) undergoing VAS with the Somatex ® intrauterine shunt system showed long-term survival beyond the neonatal period of 28 d (5/9; 55%) with varying morbidity.